Cultural Studies: Degradation of Youth's Interest in Karawitan Arts Due to Current Developments and the Role of Culture in Economic Progress in Gawok Village, Wuluhan District, Kab. Jember - Mufira, Mila; Nur Aisah, Elegi; Wakhit Yansyah, Muhamad Helmi; Rizki Mubarok, Surya (JUPE : Jurnal Pendidikan Mandala, 2024)
Culture is one of the ancestral heritage that needs to be maintained and preserved. One of the typical Javanese local cultures is karawitan. In Gawok Village, it used to be very famous for its karawitan art. Nowadays, this art is less attractive among young people, so the regeneration process of karawitan activists becomes hampered. This condition can be dangerous, even in the long term, causing the extinction of this local culture. In fact, if utilized properly this local culture, it becomes its own icon that can bring the economic life of the community forward. We will describe this phenomenon using Frederich Jamesson's thoughts on the end of capitalism. This research uses a qualitative approach.